4D-MR flow analysis in patients after repair for tetralogy of Fallot. - Geiger J; Markl M; Jung B; Grohmann J; Stiller B; Langer M; Arnold R; Geiger, J; Markl, M; Jung, B; Grohmann, J; Stiller, B; et al. (European Radiology, 2011)
Objectives: Comprehensive analysis of haemodynamics by 3D flow visualisation and retrospective flow quantification in patients after repair of tetralogy of Fallot (TOF).Methods: Time-resolved flow-sensitive 4D MRI (spatial resolution ~ 2.5 mm, temporal resolution = 38.4 ms) was acquired in ten patients after repair of TOF and in four healthy controls. Data analysis included the evaluation of haemodynamics in the aorta, the pulmonary trunk (TP) and left (lPA) and right (rPA) pulmonary arteries by 3D blood flow visualisation using particle traces, and quantitative measurements of flow velocity.Results: 3D visualisation of whole heart haemodynamics provided a comprehensive overview on flow pattern changes in TOF patients, mainly alterations in flow velocity, retrograde flow and pathological vortices. There was consistently higher blood flow in the rPA of the patients (rPA/lPA flow ratio: 2.6 ± 2.5 vs. 1.1 ± 0.1 in controls). Systolic peak velocity in the TP was higher in patients (1.9 m/s ± 0.7 m/s) than controls (0.9 m/s ± 0.1 m/s).Conclusions: 4D flow-sensitive MRI permits the comprehensive evaluation of blood flow characteristics in patients after repair of TOF. Altered flow patterns for different surgical techniques in the small patient cohort may indicate its value for patient monitoring and potentially identifying optimal surgical strategies.